Book review: Steven Blockmans (ed. coord.) Uniunea Europeană – Un proces de integrare continuă – Liber Amicorum Alfred E. Kellermann - Mihai Sebe (Romanian Journal of European Affairs, 2011)
The field of international and European law would never be the same without the enormous contribution of Professor Alfred Kellermann. In this book, dedicated to his career by his fellow colleagues, we are thus invited to read about the main topics of debate in these areas of law. The specialists as well as the general audience have to chance to learn more about the Project for a Constitution for Europe and what it implied for the European institutions (first part of the book). The second part is all about general principles and individual aspects while the last part is dedicated to the New Member States and the Eastern Europe.